KARAKTERISASI SIMPLISIA DAN SKRINING FITOKIMIA DAUN JERUK LEMON (Citrus limon (L.) Burm.f.) - Ulfayani Mayasari; Melfin Teokarsa Laoli (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2018)
Lemon Citrus (Citrus limon (L.) Burm f.) is one of the plants that has potential as a traditional medicine, and is an excellent source of vitamin C and calcium. Lemon leaf lemon can help overcome cancer, heart and liver. The purpose of this research is to characterize simplicia leaf and to know the chemical compound group contained in leaf. Characterization of simplicia include macroscopic and microscopic examination, determinations of loss on drying, determinations of water soluble extract, determination of ethanol soluble concentration, determination of total ash content, and determination of acid ash in soluble. Phytochemical screening includes the test for alkaloids, flavonoids, steroids/triterpenoids, tannins and saponins. The result obtained from examination of lemon citrus leaf characteristic gave loss on drying 69,29%; total ash content 6,40%; acid insoluble ash 1,23%; ethanol soluble extract 17,73%; water soluble extract 24,79%. The result of phytochemical screening showed that lemon leaf simplicia extract contains alkaloids, flavonoids, steroids/triterpenoids and tannins.